EVOLUTIONARY ENVIRONMENT FOR 3D MORPHOLOGICAL DESIGN - Lamas, A.; Duro, R. J. (International Journal of Computing, 2014)
This paper deals with the automation of morphological design. The system proposed here is a part of a complete automatic design system that considers the divergent and convergent stages of the design process through evolutionary procedures. The system provides a way to introduce aesthetics in the decision process. This is a difficult problem within an automatic design system, as aesthetics are subjective, depend on the opinions of humans and humans do not usually agree. The objective here is to be able to obtain the best possible aesthetic solutions for a given set of humans. This is achieved through the introduction of a set of man machine interfaces that allow the system to extract information on their relative opinions without explicitly asking them, and combines them with the engineering information provided by other simulators that participate in the design process.